Will the malaria vaccine be accepted in Pakistan after the experience of Covid-19 experience? - Hamza Nauman; Zakai, Aabia; Anusha Anwer (Journal of the Pakistan Medical Association, 2022)
Malaria, caused by Plasmodium species is transmitted by a female Anopheles mosquito. It is the second highest ranking reported disease in the public sectors in Pakistan infecting 4 million people annually.1 The struggle for a vaccine providing protection against malaria finally was successful when WHO recommended widespread usage of the newly developed RTS,S/AS01 (RTS,S) malaria vaccine for children at risk. The vaccine’s efficacy against all clinical episodes of malaria was 51% for children in the age range of 5–17 months after a year following the first 3 doses.2 ---Continue